Molecular dynamics of NH3 induced by core-electron excitation. Issue 29 (7th August 2015) - Walsh, Noelle; Sankari, Anna; Laksman, Joakim; Andersson, Tomas; Oghbaie, Shabnam; Afaneh, Feras; Månsson, Erik P.; Gisselbrecht, Mathieu; Sorensen, Stacey L.
<x xml:space="preserve">Abstract</x> Complex nuclear dynamics in the N1s−14a11 state disentangled and understood by probing the 4a1 PES via photon energy detuning.